2012
DOI: 10.1051/medsci/2012284020
|View full text |Cite
|
Sign up to set email alerts
|

BMP et cancer

Abstract: > Dans le contexte normal, les bone morphogenetic proteins (BMP), membres de la superfamille du TGF (transforming growth factor ), sont des protéines clés dans la régulation des cellules souches adultes. Ces molécules influencent l'ensemble des propriétés fonctionnelles et phé-notypiques (autorenouvellement, prolifération, différenciation, apoptose, quiescence, etc.) (Figure 1). Des études récentes démontrent également que la voie BMP est régulée par des mécanismes épigénétiques d'hypo-et hyperméthylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Several lines of evidence support a role for BMP signaling in stem cell regulation where it maintains the proliferative potential of adult stem cells (27). Recent reports demonstrate an interaction between TP63 and BMP signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence support a role for BMP signaling in stem cell regulation where it maintains the proliferative potential of adult stem cells (27). Recent reports demonstrate an interaction between TP63 and BMP signaling.…”
Section: Resultsmentioning
confidence: 99%
“…According to the context, BMPs could participate in initial tumor suppression or favor CSC maintenance and metastasis 8 . Within the BMP family, BMP2 and BMP4 have emerged as key regulators of normal and cancer SCs 11 13 . We have previously demonstrated that alterations in the BMP pathway at intrinsic (BMP receptors and downstream partners) and extrinsic (BMP extracellular ligands) levels constitute major events in transformation, expansion and persistence of immature cells in chronic phase chronic myeloid leukemia (CML) and breast cancer, by diverting their normal functions 11 , 12 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…BMP signaling affects the stem cell niche both directly and indirectly ( Zhang et al., 2003 ). Within this family, BMP2 and BMP4 are important regulators of both normal and cancer stem cells ( Laperrousaz et al., 2013; Sagorny et al., 2012 ). In breast cancer, BMP2 and BMP4 have both protumor and antitumor functions ( Balboni et al., 2013; Clement et al., 2005 ), but alterations of BMP receptors and their intracellular signal transducers SMAD1/5/8 clearly contribute to cancer progression and metastasis ( Helms et al., 2005; Katsuno et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%